2020
DOI: 10.1093/abbs/gmaa104
|View full text |Cite|
|
Sign up to set email alerts
|

iASPP protects the heart from ischemia injury by inhibiting p53 expression and cardiomyocyte apoptosis

Abstract: Currently, there remains a great need to elucidate the molecular mechanism of acute myocardial infarction in order to facilitate the development of novel therapy. Inhibitor of apoptosis-stimulating protein of p53 (iASPP) is a member of the ASPP family proteins and an evolutionarily preserved inhibitor of p53 that is involved in many cellular processes, including apoptosis of cancer cells. The purpose of this study was to investigate the possible role of iASPP in acute myocardial infarction. The protein level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…As the third member of the TP53 apoptosis stimulating protein family, its role is to inhibit the anti-tumor effect of the other two members (ASPP1 and ASPP2), leading to abnormal cell proliferation and carcinogenesis ( Li et al, 2024 ). Accordingly, it was generally believed that PPP1R13L as a novel oncogene highly expressed in a variety of tumor cells ( Yagudin et al, 2021 ). Protein Phosphatase 1 Regulatory Subunit 13 Like (PPP1R13L) is a newly identified oncoprotein previously reported to inhibit the transcriptional activity of SP1 via a direct protein-protein interaction) ( Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…As the third member of the TP53 apoptosis stimulating protein family, its role is to inhibit the anti-tumor effect of the other two members (ASPP1 and ASPP2), leading to abnormal cell proliferation and carcinogenesis ( Li et al, 2024 ). Accordingly, it was generally believed that PPP1R13L as a novel oncogene highly expressed in a variety of tumor cells ( Yagudin et al, 2021 ). Protein Phosphatase 1 Regulatory Subunit 13 Like (PPP1R13L) is a newly identified oncoprotein previously reported to inhibit the transcriptional activity of SP1 via a direct protein-protein interaction) ( Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, p53 serves to activate the tumor suppressor, mouse double minute 2 and PTEN expression-induced apoptosis [ 39 ]. In the myocardium, the activation of p53 was shown to aggravate MI injury and to increase the level of apoptosis, as determined by changes to the Bax/Bcl-2 ratio and caspase-3 activation [ 11 , 40 ]. In the present study, the level of p53 was measured to determine how the hypoxia stimulus could regulate p53-induced apoptosis in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the different influence of iASPP on p53 expression and distribution than ASPP1, knockdown of iASPP aggravates cardiac ischemic damage. 10…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the different influence of iASPP on p53 expression and distribution than ASPP1, knockdown of iASPP aggravates cardiac ischemic damage. 10 The proapoptotic effect of ASPP1 depends on its nuclear localization. Arnaud et al 33 reported that unlike in the nucleus, cytoplasmic ASPP1 competed with YAP (Yes-associated protein) for LATS2 (large tumor suppressor homolog 2) and inhibited the phosphorylation of YAP, thereby exerting an antiapoptotic effect.…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation